Spatial Planning and Transformations in the Spatial Structure of Zagreb - Vedran Prelogović; Tomislav Pintarić; Dražen Njegač (Dela, 2016)
Paper discusses the characteristics of the urban development of the City Zagreb by analysing the development of spatial planning and the changed power relations. During the last 20 years, the transformations have been mainly negative and have had important impact on changing the structure of residential, commercial and business zones, and on conversion of the industrial and military areas.